Competitive strategy : techniques for analyzing industries and competitors: with a new introduction - Porter, Michael E. (New York : Free Press, 1998)
The book explains how competitive advantage can be defined in terms of relative cost and relative prices, Porter's framework for predicting competitor behavior, his analysis of industries and his three generic strategy among others.
Originally published: New York : Free Press, c1980.
Includes bibliographical references (p. 383-387) and index.
rua 11/05/17
Loans.
Keywords: Strategic management; Competition; Industrial management